2020
DOI: 10.1063/5.0007168
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confinement of coherent acoustic phonons in transferred single-crystalline bismuth nanofilms

Abstract: Coherent acoustic phonon dynamics in single-crystalline bismuth nanofilms transferred to a glass substrate were investigated with ultrafast pump–probe spectroscopy. Coherent phonon signals were substantially enhanced by more than four times when compared with as-grown films on Si (111) substrates. Furthermore, more than 10% reduction of the acoustic phonon velocity was observed when the film thickness decreases to 22 nm, which is attributed to the modified phonon dispersion in extremely thin films from quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…From the temporal evolution of the radius (fig. S3), we have estimated the expansion speed of the Bi NP as ~200 m s −1 , slower than the elastic wave propagation speed of Bi with its sound velocity of 1790 m s −1 ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…From the temporal evolution of the radius (fig. S3), we have estimated the expansion speed of the Bi NP as ~200 m s −1 , slower than the elastic wave propagation speed of Bi with its sound velocity of 1790 m s −1 ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…Bimuthene is a newly reported 2D quantum material by us and other groups, which has exhibited promising potential use in nonlinear optics, topological materials, and catalysis. Although the generation of optical phonons in bulk Bi films had been previously reported, studies on the coherent phonon modulation in 2D Bi with quantum confinement effect are rather scant. In this work, we managed to generate size-dependent phonon coherence of bulk Bi, multi-layer Bi, and few-layer Bi by an ultrafast femtosecond laser pulse and made a systematic comparison thorough a combination of computation, femtosecond transient absorption, and reflectance spectroscopic methods. The results showed that with the decrease of the thickness of Bi materials, the carrier excited by a femtosecond ultrafast laser became more difficult to transfer and the chemical bond was softened, inducing shortened decoherence time and red-shifted vibration frequency.…”
mentioning
confidence: 99%
“…Recently, phonons have been used to couple distant quantum systems, facilitating quantum entanglement of two qubits (Bienfait et al, 2019). This transfer of coherent phonons has also been observed experimentally between bismuth nanofilms and a glass substrate (He et al, 2020). Studies of longitudinal optical phonons in GaAs/Al x Ga 1−x As quantum core-shell wires have shown that phonons influence the mobility of electrons, and that mobility can be achieved by core-shell wires of thicker shells (Dat and Hai, 2019).…”
Section: Introductionmentioning
confidence: 85%